Nanocarrier-mediated RNAi of CYP9A306 and CYB5R enhances susceptibility of invasive tomato pest, Tuta absoluta to cyantraniliprole - Ullah, Farman; G, Guru-Pirasanna-Pandi; Gul, Hina; Panda, Rudra Madhab; Murtaza, Ghulam; Zhang, Zhijun; Huang, Jun; Li, Xiaowei; Desneux, Nicolas; Lu, Yaobin (Frontiers in Plant Science, 2025)
Cyantraniliprole, a second-generation anthranilic diamide, is widely used to manage lepidopteran pests, including the invasive tomato pinworm Tuta absoluta (Meyrick). However, cyantraniliprole’s resistance mechanisms and associated fitness costs in T. absoluta remain underexplored. Here, we investigated the fitness costs and resistance mechanisms of cyantraniliprole-resistant strain (CyanRS) via nanocarrier-mediated RNA interference (RNAi). Results showed that the egg incubation period and developmental durations of larval and pupal stages were significantly prolonged in the CyanRS population of T. absoluta compared to the susceptible strain (SS). Further, the adult emergence, longevities of male and female, fecundity, and hatching rate were significantly reduced in CyanRS individuals. The mRNA expression levels of cytochrome b5 reductase (CYB5R) and cytochrome P450 (CYP9A306) were analyzed using RT-qPCR to explore their potential involvement in cyantraniliprole resistance in T. absoluta. Phylogenetic and motif analysis of CYB5R and CYP9A306 indicated their evolutionary and functional conservation with other insect species, especially Lepidopterans. Notably, nanocarrier-encapsulated dsRNA targeting CYB5R and CYP9A306 genes significantly reduced their expression levels. Further, the activity of cytochrome P450 was substantially decreased after the knockdown of the CYB5R and CYP9A306 genes. This increased susceptibility of the resistant population of T. absoluta to cyantraniliprole, leading to a higher mortality rate than the controls. These findings show that CYB5R and CYP9A306 might play a key role in cyantraniliprole resistance evolution in T. absoluta. The current study provides in-depth insights to understand the underlying mechanisms of cyantraniliprole resistance in this key invasive herbivore.